A dictionary of locutions from liturgical books by protopriest A. I. Nevostruyev - Maria Davydenkova (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2018)
This paper contains another part of dictionary entries beginning in the letter M. The characteristic features of the publication of this Dictionary, the lists of sources, abbreviations and symbols were described in detail in the previous issues of St. Tikhon’s University Review. All previously published parts of the Dictionary together with thecritical apparatus can be found at the website of the Faculty of Philology at St. Tikhon’s University for the Humanities: http://pstgu.ru/faculties/philological/science/slov_Nevostr/